STANDARDISATION AND PHYTOCHEMICAL SCREENING OF TRADITIONAL FORMULATION - Ramamoorthy, Sri Kamatchi Priya; Manickam, Diwakar; Subramaniam, Samu; Subramaniam, Shyama (International Journal of Current Pharmaceutical Research, 2016)
Objective: The main objective of this study is to standardise and evaluate traditional formulation both qualitatively and quantitatively on the basis of organoleptic characteristics, physical characteristics, physiochemical properties and phytochemical screening. Methods: Traditional formulation (TF) containing seven traditionally used herbs were collected from local areas and market. The plants were washed, air-dried and coarsely powdered. The aqueous extract was prepared as per literature, and various physiochemical, phytochemical screening was done. Results: The organoleptic character shows the drug with greenish colour, slightly bitter taste and characteristic odour. The physiochemical properties show the appropriate pH and the solubility of TF. Secondary metabolites like phenolic compounds and flavonoids are present abundantly in aqueous extract than in other extracts. Conclusion: Our studies suggests that TF contains medicinally important secondary metabolites which has disease protective properties. This study will help in the progression of a suitable monograph, determining the quality and purity of a crude extract and laying down pharmacopoeia standards for the formulation.